Failure to Obtain Computed Tomography Imaging in Head Trauma: A Review of Relevant Case Law. (17th November 2015) - Lindor, Rachel A.; Boie, Eric T.; Campbell, Ronna L.; Hess, Erik P.; Sadosty, Annie T.
Abstract: Objectives: The objectives were to describe lawsuits against providers for failing to order head computed tomography (CT) in cases of head trauma and to determine the potential effects of available clinical decision rules (CDRs) on each lawsuit. Methods: The authors collected jury verdicts, settlements, and court opinions regarding alleged malpractice for failure to order head CT in the setting of head trauma from 1972 through February 2014 from an online legal research tool (WestlawNext). Data were abstracted onto a standardized data form. The performance of five CDRs was evaluated. Results: Sixty relevant cases were identified (52 adult, eight children). Of 48 cases with known outcomes, providers were found negligent in 10 cases (six adult, four pediatric), settled in 11 cases (nine adult, two pediatric), and were found not liable in 27 cases. In all 10 cases in which providers were found negligent, every applicable CDR studied would have indicated the need for head CT. In all eight cases involving children, the applicable CDR would have suggested the need for head CT or observation. Conclusions: A review of legal cases reported in a major online legal research system revealed 60 lawsuits in which providers were sued for failing to order head CTs in cases of head trauma. In all cases in which providers were found negligent, CT imaging or observation would have been indicated by every applicable CDR.